Chapter The Court and Administration of Karkemish in the Late Bronze Age - MORA, CLELIA (Studia Asiana, 2023)
The purpose of this paper is to update the study and analysis of the administration of Karkemish during the final phase of the Hittite kingdom. The first introductory part outlines previous contributions and results. The second part presents the updated lists of princes and officials belonging to the court of Karkemish. The third part attempts to place princes and officials in chronological order (according to the different periods of reigns). Lastly, the fourth part provides an in-depth prosopographic analysis regarding some important or interesting officials.